问题
解答题
(1)
(2)3
(3)(-81)÷2
(4)23×(-5)-(-3)÷
(5)19×
(6)
(7)(-36
(8)(
|
答案
(1)
+(-1 2
)+2 3
+(-4 5
)+(-1 2
)1 3
=[
+(-1 2
)]+[(-1 2
)+(-2 3
)]+1 3 4 5
=0-1+4 5
=-
; 1 5
(2)3
-(-15)-(-31 4
)+(-15)1 8
=3
+15+31 4
-151 8
=6
;3 8
(3)(-81)÷2
×1 4
÷(-16)4 9
=(-81)×
×4 9
×(-4 9
)1 16
=1;
(4)23×(-5)-(-3)÷3 128
=-115-(-3)×128 3
=-115+128
=13;
(5)19×
-0.4×(-18)+2 5
×(-19)2 5
=19×
-2 5
×(-18)+2 5
×(-19)2 5
=
(19+18-19)2 5
=
×182 5
=
;36 5
(6)
÷(1 18
+2 3
-1 6
)1 2
=
×1 18
+3 2
×6-1 18
×21 18
=
+1 12
-1 3 1 9
=
+3 36
-12 36 4 36
=
;11 36
(7)(-36
)÷99 11
=(-
)×405 11 1 9
=-
;45 11
(8)(
-1)×(1 50
-1)×(1 49
-1)×…×(1 48
-1)×(1 4
-1)×(1 3
-1)1 2
=(-
)×(-49 50
)(-48 49
)×…×(-47 48
)(-3 4
)(-2 3
)1 2
=
.1 50